Water treatment fluorine removal agent as well as preparation method and application thereof

By using a combination technology of a variety of metal salt precursors and nanomaterials, the problem of poor fluorine ion removal effect of existing fluorine removers when treating etching wastewater is solved, and efficient removal of fluorine, copper and iron ions is achieved, meeting emission standards and improving treatment efficiency.

CN119551788APending Publication Date: 2025-03-04ZIBO ZHIYAN ENVIRONMENTAL PROTECTION TECH CO LTD +1

Patent Information

Application Number
CN202510095587.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

When existing fluorine-deductors treat etching wastewater, the fluorine ion removal effect is poor, especially affected by copper and iron ions, which makes it difficult to meet emission standards.

Method used

Various metal salt precursors are used to produce different forms of binding reactions with fluorine ions. By enhancing complexing by magnesium chloride, zinc chloride, etc., polymerized aluminum chloride participates in the removal of fluorine and reaction with copper and iron ions, and combines titanium dioxide nanotubes, activated alumina and other materials to achieve effective removal of multiple ions.

Benefits of technology

It significantly improves the removal rate of fluorine ions, takes into account the removal of copper and iron ions or reduces its impact on fluorine removal, ensures that the water quality after treatment meets the emission standards, and improves the efficiency of the treatment process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of water treatment fluorine removal agent production, in particular to a water treatment fluorine removal agent and a preparation method and application thereof. Specific raw materials are added and reasonable treatment steps are adopted for the wastewater containing fluorine, copper and iron ions generated in the semiconductor chip manufacturing etching process, so that the fluorine ions can be effectively removed; the method can remove copper and iron ions or reduce the influence of the copper and iron ions on fluorine removal (especially wastewater simply treated by sodium sulfide which is specially used for removing copper and iron ions), and has strong pertinence and applicability to etching wastewater with specific water quality; the method is good in collaboration, has both operability and flexibility, and ensures the treatment effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water treatment defluorination agent production, in particular to a water treatment defluorination agent and a preparation method and application thereof. Background Art

[0002] In the etching process of semiconductor chip manufacturing, etching is a key step in removing unnecessary materials on the surface of the wafer after photolithography. This process often uses fluorine-containing chemicals such as hydrofluoric acid to etch the oxide layer of the silicon wafer. In order to accurately control the etching depth and shape, etching solutions containing metal ions such as copper and iron are also used. This results in the generation of wastewater containing high concentrations of fluorine, copper, and iron ions during cleaning after etching.

[0003] The existing defluorination agent is not very effective in removing fluoride ions when treating this type of etching wastewater, especially due to the interference of copper and iron ions. 2+ ) Regardless of the fluoride content, it can react with fluoride ions to form a complex. The resulting complex will hinder the reaction between fluoride ions and defluoridation agents, thereby reducing the removal rate of fluoride ions. 3+ ) will also form stable complexes with fluoride ions, seriously interfering with the precipitation or adsorption removal process of fluoride ions, making it difficult to effectively remove fluoride ions.

[0004] In addition, copper ions (Cu 2+ ), iron ions (Fe 3+ ) and other heavy metal ions, usually need to be removed separately with the help of specific methods. If the removal is not thorough, copper ions and iron ions will react with fluoride ions, and the resulting complex will hinder the reaction of fluoride ions with defluoridation agents, thereby reducing the removal rate of fluoride ions. The existing technology mostly uses chemical precipitation methods, adding precipitants such as sodium sulfide or sodium hydroxide to wastewater, copper ions will react with sodium sulfide to form copper sulfide precipitates, and under appropriate pH conditions, iron ions can also form iron hydroxide precipitates. Through precipitation separation operations, copper ions and iron ions can be effectively removed, reducing their impact on fluoride ion removal. However, the removal conditions of these heavy metal ions are different from those of fluoride ions. If they are not treated separately, it is extremely difficult to meet the corresponding emission standards. Ion exchange and adsorption methods (such as using adsorption materials such as activated carbon and ion exchange resins) are also commonly used to remove these heavy metal ions, but in actual applications, it is necessary to reasonably select and optimize the treatment methods based on the specific water quality and treatment requirements of the wastewater to ensure that pollutants such as fluoride ions, copper ions, and nickel ions in etching wastewater can be effectively removed, so that the treated water quality meets the emission standards. Summary of the invention

[0005] In view of the above deficiencies in the prior art, the purpose of the present invention is to provide a water treatment defluoridation agent, which uses a variety of metal salt precursors to produce different forms of binding reactions with fluoride ions, magnesium chloride and zinc chloride to enhance complexation, and polyaluminum ferric chloride to participate in defluorination and reaction with copper and iron ions, thereby achieving effective removal of multiple ions; and different raw materials cooperate with each other to play a synergistic role, greatly improving the treatment capacity of complex etching wastewater.

[0006] Another object of the present invention is to provide a method for preparing a water treatment defluorinating agent, in which the design of various conditions is more scientific and reasonable, which can promote the full reaction of raw materials, optimize the product structure, and improve the performance of the defluorinating agent.

[0007] The third object of the present invention is to provide an application of a water treatment defluorination agent, which shortens the flocculation reaction time, sedimentation time and solid-liquid separation time, and significantly improves the efficiency of the overall treatment process while ensuring the treatment effect.

[0008] The present invention is achieved by adopting the following technical solutions: The preparation method of the water treatment defluoridation agent comprises the following steps: (1) Weigh dried lanthanum chloride, cerium sulfate, yttrium acetate, magnesium chloride, zinc chloride, and potassium fluorozirconate respectively, place in a beaker, add deionized water and stir to form a mixed salt solution. Use a magnetic stirrer during the stirring process at a speed of 400-600 r / min, and continue stirring for 1.5-2.5 hours; (2) adding cerium-doped titanium dioxide nanotubes to a mixed salt solution, stirring at 50-60° C. at a speed of 350-450 r / min for 7-9 hours, and continuously introducing nitrogen during the reaction to obtain a mixed solution; (3) Add 3-4 mol / L ammonia water dropwise to the mixed solution obtained in step (2), adjust the pH value to 9-10, continue stirring for 5-7 hours, then transfer it to a centrifuge tube, centrifuge it at a speed of 8000-10000 r / min for 20-30 minutes, discard the supernatant, and repeatedly wash the precipitate with deionized water for 8-15 times; (4) The washed precipitate is transferred to an oven, dried at 130-150°C for 8-12 hours, and then placed in a tube furnace and calcined at 550-650°C for 6-8 hours with nitrogen to obtain a titanium dioxide nanotube intermediate product loaded with lanthanum, cerium, yttrium, magnesium, zinc and zirconium. During the calcination process, the heating rate is 5-7°C / min and the cooling rate is 3-5°C / min; (5) The intermediate product is mixed with pretreated activated alumina, diluted and aged polyaluminium chloride iron, microwave-treated hydroxyapatite loaded iron, and sieved and graded chitosan-bentonite composite adsorbent loaded with aluminium and iron, deionized water is added, and the mixture is stirred at a speed of 1200-1800 r / min for 3-5 hours in a high-speed stirrer. At the same time, sodium polyacrylate is added in an amount of 0.1%-0.2% of the total mass of the raw materials. The mixed material is dried in an oven at 65-75°C to constant weight, and then ground into fine powder with a particle size of less than 160 mesh, thereby obtaining a water treatment defluoridation agent. The total mass of the raw materials is the sum of the mass of lanthanum chloride, cerium sulfate, yttrium acetate, magnesium chloride, zinc chloride, potassium fluorozirconate, cerium-doped titanium dioxide nanotubes, sodium polyacrylate, pretreated activated alumina, diluted and aged polyaluminium chloride iron, microwave-treated hydroxyapatite loaded iron, and sieved and graded chitosan-bentonite composite adsorbent loaded with aluminium and iron.

[0009] In step (1), lanthanum chloride is placed in a dryer for 3-7 days to balance the moisture before weighing to minimize the weighing error caused by moisture absorption; cerium sulfate is dried and balanced before weighing to ensure its stability and reactivity; yttrium acetate needs to be fully dried before weighing. The complexation of magnesium chloride and fluoride ions helps to remove fluoride, and it is dried before use. Zinc chloride is dried to improve its reactivity in the system. The zirconium ions in potassium fluorozirconate have a strong binding ability with fluoride ions, which can generate more stable fluorine-containing compounds and greatly enhance the defluorination performance. In step (5), activated alumina particles with a particle size of 0.2-1 mm are selected. This smaller particle size can provide a larger specific surface area. After rinsing with deionized water for 4-8 times to remove impurities such as dust on the surface, soak it in dilute hydrochloric acid (0.1-0.2 mol / L, soaking for 30-50 minutes) to further activate the surface, then rinse it with deionized water until neutral, and dry it in an oven at 120-140°C for 4-6 hours. The commercially available polyaluminium ferric chloride was diluted to an Al2O3 content of 5%-7%, and aged at room temperature at a stirring speed of 150-250 r / min for 2-3 hours.

[0010] Lanthanum, cerium, and yttrium ions released by different metal salts such as lanthanum chloride, cerium sulfate, and yttrium acetate can combine with fluoride ions in different forms. Lanthanum ions and fluoride ions form lanthanum fluoride precipitates, cerium ions can form complexes with fluoride ions, and yttrium ions can also combine with fluoride ions to form insoluble compounds. These different reaction modes increase the ways in which fluoride ions are removed. With the addition of magnesium chloride and zinc chloride, magnesium ions and zinc ions can complex with fluoride ions, and their hydroxide precipitation has an adsorption effect on fluoride ions, which cooperates with other metal ions to expand the capture range of fluoride ions. The iron and aluminum ions in polyaluminum ferric chloride participate in the defluorination reaction on the one hand, and lay the foundation for the subsequent reaction with copper and iron ions on the other hand. The amino groups on the surface of titanium dioxide nanotubes treated with surface amino can coordinate with metal ions in metal salt precursors. This coordination effect is like a "hook", which firmly loads metal ions on the surface of titanium dioxide nanotubes, greatly improving the loading amount and stability of metal ions.

[0011] After activated by soaking in dilute hydrochloric acid, the number of active sites on the surface of activated alumina increases. After mixing with other raw materials, its adsorption capacity for fluoride ions is enhanced, and it can synergistically remove fluoride with the metal ions produced by the metal salt precursor. At the same time, its adsorption of impurities in wastewater helps to purify water quality and provide a more "clean" environment for other raw materials to play a better role. The hydrolysis products of polyaluminum ferric chloride (PAFC) after dilution and aging are stable. The hydroxyl complex produced by the hydrolysis of aluminum and iron ions can complex with fluoride ions, and can also flocculate and adsorb with copper and iron ions. When compounded with other raw materials, it can promote the formation and sedimentation of precipitation. For example, combined with titanium dioxide nanotubes loaded with metal ions, the colloidal substances of PAFC can be adsorbed on the surface of nanotubes to capture fluoride, copper, and iron ions together to improve the removal efficiency. Take sodium sulfide, a raw material specifically used to treat copper and iron ions, as an example. When sodium sulfide reacts with etching wastewater to generate copper sulfide and iron sulfide precipitates, the surfaces of these precipitates are charged. At this time, raw materials such as titanium dioxide nanotubes loaded with metal ions, polyaluminium chloride iron, and hydroxyapatite loaded with iron can be combined with the precipitate through electrostatic adsorption, chemical complexation, etc. For example, the hydrolysis product of PAFC can be adsorbed on the surface of copper sulfide and iron sulfide precipitates, and through electrical neutralization and bridging, the precipitate particles can be aggregated and grown, accelerating the precipitation rate. Activated alumina, chitosan-bentonite composite adsorbent loaded with aluminium iron (CT-B-Al-Fe), etc. can also provide more attachment sites for precipitation, improving the removal efficiency of copper and iron ions. At the same time, these raw materials have no effect on the removal of fluoride ions. On the contrary, due to the efficient removal of copper and iron ions, the interference with the defluorination reaction is reduced, making the overall removal of fluoride, copper, and iron ions better.

[0012] When activated alumina is mixed with sodium sulfide, a special remover for removing copper and iron ions, the two can promote each other. The surface properties of copper sulfide and iron sulfide precipitates generated by the reaction of sodium sulfide with copper and iron ions can change, making them easier to be adsorbed by activated alumina. Activated alumina can provide more attachment sites for precipitation, making the precipitation particles aggregate larger, accelerating the precipitation process, and thus improving the removal efficiency of copper and iron ions. At the same time, since copper and iron ions are removed more efficiently, their competition for the active sites of activated alumina for adsorbing fluoride ions is reduced, so that the removal efficiency of activated alumina for fluoride ions can also be improved to a certain extent. When combined with sodium sulfide, the colloid produced by PAFC hydrolysis can promote the coagulation and sedimentation of copper sulfide and iron sulfide precipitation. Its hydrolysis products can be adsorbed on the surface of precipitation particles, and through electrical neutralization and bridging, the precipitation particles are aggregated and grown, the precipitation speed is accelerated, and the removal effect of copper and iron ions is improved.

[0013] In the steps (1) and (2), the weight proportions of the raw materials are as follows: 10-15 parts of lanthanum chloride; 6-12 parts of cerium sulfate; 7-10 parts of yttrium acetate, 6-8 parts of magnesium chloride, 4-6 parts of zinc chloride, 5-7 parts of potassium fluorozirconate, and 400-600 parts of deionized water; 35-42 parts of cerium-doped titanium dioxide nanotubes; in the step (5), the amount of activated alumina added after pretreatment is 1.2-1.8 times the mass of the intermediate product; the amount of polyaluminium ferric chloride added after dilution and aging is 0.6-1 times the volume of the intermediate product; the amount of hydroxyapatite loaded with iron added after microwave treatment is 0.2-0.3 times the mass of the intermediate product; and the amount of chitosan-bentonite composite adsorbent loaded with aluminium and iron added after sieving and grading is 0.15-0.25 times the mass of the intermediate product.

[0014] The purity of the lanthanum chloride, cerium sulfate, yttrium acetate, magnesium chloride and zinc chloride is greater than or equal to 99%, the purity of potassium fluorozirconate is ≥98%, the particle size of the pretreated activated alumina is 0.2-1mm, and the Al2O3 content in the polyaluminum ferric chloride is 5%-7%.

[0015] The method for preparing cerium-doped titanium dioxide nanotubes comprises the following steps: ① Mix 0.5g of ammonium fluoride, 5g of deionized water and 95g of ethylene glycol, then add 0.05mol / L of hexadecyltrimethylammonium bromide and continue stirring until completely dissolved to obtain an electrolyte; ②Use titanium foil as anode and platinum sheet as cathode, place them in electrolyte, and carry out anodic oxidation reaction at a constant voltage of 25V for 2h. Keep the electrolyte temperature at 25℃ during the reaction; ③ Take out the anodized sample, rinse it with deionized water, and then soak it in an ethanol solution containing 0.01 mol / L cerium nitrate for 1-2 hours. The mass fraction of cerium in the titanium dioxide nanotubes after doping is 2-5%; ④ Dry the sample obtained in step ③ in an oven at 60-65°C for 12 hours, then place it in a tubular furnace, heat it to 550°C at a heating rate of 5°C / min under a nitrogen atmosphere, and calcine it for 3 hours to obtain cerium-doped titanium dioxide nanotubes.

[0016] Titanium dioxide nanotubes treated with surface amino groups are used as carriers. The amino groups on the surface coordinate with the metal ions in the metal salt precursor, firmly loading the metal ions on their surface. This not only improves the dispersibility of the metal ions, but also enables them to play a more stable role in subsequent reactions. During the loading process, the high specific surface area of ​​the nanotubes also provides more contact opportunities for the reaction between metal ions and fluoride ions.

[0017] The method for preparing the microwave-treated hydroxyapatite loaded with iron comprises the following steps: a. Synthesis of hydroxyapatite precursor: Weigh calcium nitrate and dissolve it in deionized water to prepare a 0.5-1 mol / L solution, stir it evenly, and control the temperature at 50-60°C; dissolve diammonium hydrogen phosphate in another part of deionized water to prepare a 0.3-0.6 mol / L solution, stir it evenly, and keep the temperature at 50-60°C; add the diammonium hydrogen phosphate solution dropwise to the calcium nitrate solution at a stirring speed of 600-800 r / min, and control the dropping speed at 1-3 mL / min. After the dropping is completed, continue to stir and react for 3-5 hours to form a hydroxyapatite precursor suspension; b. Loading iron and fluoride ion doping: Dissolve ferric nitrate in deionized water to prepare a 0.1-0.3 mol / L solution, add it to the hydroxyapatite precursor suspension, and continue stirring at a speed of 400-600 r / min for 2-3 hours; dissolve the weighed sodium fluoride in deionized water to prepare a 0.05-0.1 mol / L solution, add it to the reaction system, and continue stirring for 1-2 hours to obtain a suspension; c. Precipitation, washing and drying: The suspension obtained in step b is transferred to a centrifuge tube, centrifuged at a speed of 4000-6000 r / min for 15-25 min, and the precipitate is collected; the precipitate is repeatedly washed with deionized water for 5-8 times, centrifuged again after each washing, and finally the precipitate is washed with anhydrous ethanol for 1-2 times; the washed precipitate is transferred to an oven, and dried at 100-120° C. for 8-12 h to obtain a dried Fe-HAP powder; d. Grinding and microwave treatment: The dried Fe-HAP powder is ground to a particle size less than 100 meshes; the ground powder is placed in a microwave device and treated at a power of 300-500W for 6-10 minutes to obtain microwave-treated hydroxyapatite loaded with iron.

[0018] The purity of the diammonium hydrogen phosphate and calcium nitrate is greater than or equal to 99%, and the calcium-phosphorus molar ratio Ca / P is 1.67; the purity of the ferric nitrate is ≥99%; the mass of the loaded iron element accounts for 8%-12% of the mass of the hydroxyapatite; the purity of the sodium fluoride is ≥99%, and the added amount is 0.5%-2% of the mass of the hydroxyapatite.

[0019] The activity of hydroxyapatite loaded with iron (Fe-HAP) after microwave treatment is greatly increased. Hydroxyapatite itself has the ability to exchange and adsorb fluoride ions, and the loaded iron ions can also form complexes with fluoride ions, further enhancing the defluorination effect. Moreover, it also has a certain adsorption and coprecipitation effect on copper and iron ions. In combination with other raw materials, such as polyaluminium chloride ferric, it can adsorb and precipitate copper and iron ions together, improving the removal capacity of multiple ions. When combined with reagents specifically for removing copper and iron ions (such as sodium hydroxide for generating hydroxide precipitation), the presence of Fe-HAP can provide more adsorption sites for the hydroxide precipitation of copper and iron ions, making the precipitation easier to settle. At the same time, the iron ions on its surface may also participate in the reaction process with copper and iron ions, for example, through oxidation-reduction or coprecipitation, to enhance the removal of copper and iron ions.

[0020] The preparation method of the chitosan-bentonite composite adsorbent loaded with aluminum and iron comprises the following steps: Ⅰ. Dissolve chitosan with a deacetylation degree of ≥90% in an acetic acid solution with a mass percentage concentration of 1%-3% to prepare a chitosan solution with a mass fraction of 1%-2%, and stir until it is completely dissolved; select sodium bentonite, pass it through a 200-mesh sieve to remove large particle impurities; prepare aluminum sulfate and iron sulfate with a purity of ≥99%; Ⅱ. Add the sieved sodium bentonite to a hydrochloric acid solution with a concentration of 0.5-1 mol / L, with a solid-liquid ratio of 1:10-1:15, and stir the reaction at 60-80°C for 2-3 hours to perform activation treatment; after the reaction, centrifuge at a speed of 4000-5000 r / min for 10-15 minutes, and then dry at 100-120°C for 6-8 hours; add the dried sodium bentonite to ionized water to prepare a mass fraction of 5 %-10% suspension; under a stirring speed of 400-600r / min, a mixed solution of 0.1-0.5mol / L aluminum sulfate and 0.05-0.3mol / L ferric sulfate is added to the bentonite suspension, the reaction temperature is controlled at 40-50°C, the reaction time is 3-5h, wherein the ratio of the amount of aluminum and iron ions to the amount of exchangeable cations in the bentonite is (0.5-1.5): 1, to obtain an aluminum and iron loaded bentonite suspension; III. Mix the aluminum-iron loaded bentonite suspension with the previously prepared chitosan solution, and continue stirring at 40-50°C, at a stirring speed of 300-500r / min, for 6-10h; pour the mixed material into a mold to form granules or blocks, and then air-dry at room temperature to a preliminary shape; transfer the preliminary formed material to an oven and dry it at 60-80°C to constant weight; IV. The dried material was crushed to a particle size of less than 200 mesh; it was sieved and classified twice, the first time using a 150-mesh sieve to remove larger particles, and the second time using a 200-mesh sieve to further screen, to obtain chitosan-bentonite composite adsorbent loaded aluminum iron fine powder with uniform particle size.

[0021] The prepared Fe-HAP and CT-B-Al-Fe can work synergistically with other raw materials in the overall solution. For example, the iron ions loaded by Fe-HAP can work together with the metal ions loaded by titanium dioxide nanotubes to produce adsorption and precipitation effects on fluorine, copper, and iron ions; chitosan and bentonite in CT-B-Al-Fe can work together with activated alumina to increase adsorption sites and improve the removal effect of various ions. Chitosan-bentonite composite adsorbent loaded with aluminum and iron (CT-B-Al-Fe) was prepared in a constant temperature water bath to ensure uniform loading of aluminum and iron. The amino and hydroxyl groups of chitosan can complex with copper, iron, and fluoride ions, and bentonite has a large specific surface area and ion exchange capacity. The loaded aluminum and iron ions also participate in the reaction. The synergistic effect of each component, when mixed with other raw materials, can further enhance the removal ability of fluoride ions, while strengthening the removal effect of copper and iron ions. For example, in combination with activated alumina, the adsorption characteristics of each can be used to remove fluorine, copper, and iron ions in an all-round way. When acting together with sodium sulfide on wastewater, the chitosan in CT-B-Al-Fe can complex with copper and iron ions, and the bentonite provides adsorption sites. The loaded aluminum and iron ions can promote the formation and aggregation of copper sulfide and iron sulfide precipitation. Moreover, its composite structure can make the flocs in the reaction system more stable and improve the removal efficiency of copper and iron ions.

[0022] The water treatment defluoridation agent is prepared by the above water treatment defluoridation agent preparation method.

[0023] The water treatment defluoridation agent is used for defluoridating wastewater containing fluorine, copper and iron ions generated by etching process in the process of manufacturing semiconductor chips.

[0024] The defluorination process comprises the following steps: A. Use ion chromatography to accurately determine the concentration of fluoride ions in etching wastewater, which is between 100-1000 mg / L; determine the concentration of copper and iron ions by atomic absorption spectroscopy; determine the pH value of wastewater; weigh EDTA-2Na according to 1.5-2 times the total molar amount of copper and iron ions; prepare it into a 0.1-0.2 mol / L solution, add it to etching wastewater at a stirring speed of 300r / min, and react for 20-30 minutes. If the pH value of the wastewater increases after being treated with sodium sulfide, use 1-2 mol / L hydrochloric acid solution to adjust the pH value to 6-8; if the pH value does not change much and is within the range of 6-8, no adjustment is required; B. According to the measured fluoride ion concentration, determine the dosage of the defluoridation agent: when the fluoride ion concentration is 100-300mg / L, the dosage is 4-6g / L; when it is 300-600mg / L, the dosage is 6-8g / L; when it is 600-1000mg / L, the dosage is 8-12g / L; C. Maintain the reaction temperature at 25-35°C and the reaction time at 90-150min; use mechanical or magnetic stirring, and control the stirring speed at 250-350r / min; set the speed at 350r / min at the beginning, and adjust it to 250-300r / min after 30min of reaction; D. 30 minutes after the reaction starts, add nano-silicon dioxide according to the mass of the defluorinating agent at 3%-5%; the nano-silicon dioxide is ultrasonically dispersed in anhydrous ethanol in advance, the ultrasonic power is 250-350W, and the ultrasonication is carried out for 30-40 minutes; stirring is continued for 30-40 minutes after addition; when the defluorination reaction is carried out for 60 minutes, a polyacrylamide solution with a mass percentage concentration of 0.1%-0.3% is added, and the addition amount is 0.5-1.5mL / L; after adding the polyacrylamide solution, a polydopamine solution is added according to the total mass of the system at 1%-2%; the polydopamine solution is prepared by stirring dopamine hydrochloride in a Tris-HCl buffer solution at room temperature for 24 hours, and stirring is carried out for 20-30 minutes after addition, wherein the pH of the Tris-HCl buffer solution is 8.5; E. After stopping stirring, let it stand and settle for 45-60 minutes; then use filter paper with a pore size of 0.45-0.6μm to filter at normal pressure; then transfer the filtrate to a centrifuge tube and centrifuge it at a speed of 4000-6000r / min for 10-20min to separate the remaining fine particles and obtain treated water.

[0025] Nano-silica has a high specific surface area and abundant surface hydroxyl groups. After addition, it can provide additional adsorption sites for fluoride ions. Its surface hydroxyl groups can also interact with metal ions in the defluoridation agent to enhance the defluoridation effect. The polydopamine solution should be stored in a brown bottle. If it is used in the short term, it can be placed in a 4°C refrigerator. For long-term storage, it needs to be frozen in a -20°C refrigerator. It needs to be slowly thawed at room temperature and shaken well before use.

[0026] Determine the amount of EDTA-2Na added according to the concentration of copper and iron ions. At this ratio, it can effectively chelate copper and iron ions without wasting reagents. At the same time, when the copper ion concentration is higher than 300 mg / L and the iron ion concentration is higher than 500 mg / L, take a 2-fold molar ratio; when the copper ion concentration is lower than 200 mg / L and the iron ion concentration is lower than 300 mg / L, take a 1.5-fold molar ratio. Monitor the wastewater quality regularly. When the fluoride ion concentration fluctuates by more than ±20%, re-conduct a small test and adjust the defluoridation agent dosage, reaction time and other parameters according to the experimental results.

[0027] EDTA-2Na mainly acts on residual copper and iron ions. When copper and iron ions exist, they may compete with the active sites in the defluoridation agent for adsorption, affecting the defluoridation agent's removal effect on fluoride ions. EDTA-2Na can form stable chelates with copper and iron ions, "isolating" these metal ions from a state that may interfere with the defluoridation reaction. In this way, the defluoridation agent can react more focusedly with fluoride ions. For example, the process of lanthanum, cerium and other ions in the defluoridation agent forming insoluble precipitates or stable complexes with fluoride ions will not be disturbed too much, thereby improving the defluoridation efficiency of the defluoridation agent. Nano-silica has a high specific surface area and abundant surface hydroxyl groups. After being added to the reaction system, on the one hand, its high specific surface area provides additional adsorption sites for fluoride ions, increasing the chance of fluoride ions being adsorbed. On the other hand, the hydroxyl groups on the surface of nano-silica can interact with metal ions in the defluoridation agent (such as lanthanum, cerium, etc. loaded on titanium dioxide nanotubes), and closely link nano-silica and the defluoridation agent through chemical bonding or physical adsorption. In this way, when the defluoridation agent plays a role in removing fluoride ions, nano-silica can participate in synergy, expand the effective range of defluoridation, and further improve the overall defluoridation effect. Polydopamine has good adhesion and rich functional groups. In the flocculation and precipitation stage, polydopamine first connects the fine sediment particles generated by the defluoridation reaction through its adhesion, which promotes the agglomeration of the sediment. At the same time, the functional groups on polydopamine, such as amino groups and phenolic hydroxyl groups, can react with the metal ions in the defluoridation agent and the ions on the surface of the sediment to enhance the binding force between the sediments. This makes the precipitation process faster and more thorough, which helps to improve the efficiency of solid-liquid separation, thereby indirectly improving the actual application effect of the defluoridation agent. Because more efficient solid-liquid separation can reduce the solid impurities remaining in the treated water, reduce the risk of fluoride ions dissolving again into the water body, and ensure that the final fluoride ion concentration of the effluent meets the discharge standard. The addition of polyacrylamide (PAM) enables these fine particles to aggregate quickly and accelerate the precipitation process. This is coordinated with the defluorination process of the defluoridation agent, ensuring that the precipitate produced by the defluorination reaction can be separated from the water body in a timely manner, maintaining the positive progress of the defluorination reaction and improving the utilization efficiency of the defluoridation agent.

[0028] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention is aimed at wastewater containing fluorine, copper and iron ions generated by the etching process of semiconductor chip manufacturing. By adding specific raw materials and adopting reasonable treatment steps, it can not only effectively remove fluorine ions, but also take into account the removal of copper and iron ions or reduce their influence on fluorine removal (especially for wastewater that has been simply treated with a remover such as sodium sulfide that specifically removes copper and iron ions). It has strong pertinence and applicability for etching wastewater of specific water quality; it has good synergy, and has both operability and flexibility, thereby ensuring the treatment effect.

[0029] (2) The defluoridation agent obtained by the present invention is composed of various components such as various metal salt precursors, cerium-doped titanium dioxide nanotubes, activated alumina, polyaluminium chloride iron, hydroxyapatite loaded iron, chitosan-bentonite composite adsorbent loaded aluminum iron, etc. These components react with fluoride ions through different mechanisms, such as forming precipitation, complexation, etc., and the various components work together to greatly improve the removal effect of fluoride ions. The defluoridation agent has good adaptability to the complex ion components in etching wastewater, especially the interference of copper and iron ions. Through the synergistic effect of various components, the influence of copper and iron ions on the removal of fluoride ions can be reduced. Even when the concentration of copper and iron ions is high, the effective removal of fluoride ions can still be guaranteed, so that the treated water quality meets the discharge standard, and the adsorption performance is excellent.

[0030] (3) In the various steps of preparing the defluorinating agent of the present invention, the reaction conditions are designed scientifically and reasonably. Through reasonable step arrangement and condition control, the raw materials can be fully reacted, the unreacted raw material residue can be reduced, the utilization rate of the raw materials can be improved, and the performance of the defluorinating agent product can be guaranteed to be stable.

[0031] (4) In the application process, the present invention shortens the flocculation reaction time, sedimentation time and solid-liquid separation time by optimizing the time and conditions of each treatment step, thereby significantly improving the efficiency of the overall treatment process, and can treat etching wastewater more quickly to meet the treatment needs in actual production; it can cope with the treatment of etching wastewater of different water quality and ensure that the treated water quality meets the discharge standards. DETAILED DESCRIPTION

[0032] In order to make the purpose and technical solution of the present invention more clear, the present invention is further described in detail below.

[0033] Example 1 The method for preparing cerium-doped titanium dioxide nanotubes comprises the following steps: ① Mix 0.5g of ammonium fluoride, 5g of deionized water and 95g of ethylene glycol, then add 0.05mol / L of hexadecyltrimethylammonium bromide and continue stirring until completely dissolved to obtain an electrolyte; ②Use titanium foil as anode and platinum sheet as cathode, place them in electrolyte, and carry out anodic oxidation reaction at a constant voltage of 25V for 2h. Keep the electrolyte temperature at 25℃ during the reaction; ③ Take out the anodized sample, rinse it with deionized water, and then soak it in an ethanol solution containing 0.01 mol / L cerium nitrate for 1 h; ④ Dry the sample obtained in step ③ in an oven at 63°C for 12 h, then place it in a tubular furnace, heat it to 550°C at a heating rate of 5°C / min under a nitrogen atmosphere, and calcine it for 3 h to obtain cerium-doped titanium dioxide nanotubes.

[0034] The method for preparing hydroxyapatite loaded with iron after microwave treatment comprises the following steps: a. Synthesis of hydroxyapatite precursor: Weigh calcium nitrate and dissolve it in deionized water to prepare a 0.8 mol / L solution, stir it evenly, and control the temperature at 55°C; dissolve diammonium hydrogen phosphate in another part of deionized water to prepare a 0.5 mol / L solution, stir it evenly, and keep the temperature at 55°C; add the diammonium hydrogen phosphate solution dropwise to the calcium nitrate solution at a stirring speed of 700 r / min, and control the dropping speed at 2 mL / min. After the dropping is completed, continue to stir and react for 4 hours to form a hydroxyapatite precursor suspension; b. Loading iron and fluoride ion doping: Dissolve ferric nitrate in deionized water to prepare a 0.2 mol / L solution, add it to the hydroxyapatite precursor suspension, and continue stirring at a stirring speed of 500 r / min for 2 hours; dissolve the weighed sodium fluoride in deionized water to prepare a 0.08 mol / L solution, add it to the reaction system, and continue stirring for 1 hour to obtain a suspension; c. Precipitation, washing and drying: The suspension obtained in step b was transferred to a centrifuge tube, and centrifuged at a speed of 5000 r / min for 20 min to collect the precipitate; the precipitate was repeatedly washed with deionized water for 8 times, and centrifuged again after each washing, and finally the precipitate was washed twice with anhydrous ethanol; the washed precipitate was transferred to an oven and dried at 110° C. for 10 h to obtain a dried Fe-HAP powder; d. Grinding and microwave treatment: The dried Fe-HAP powder was ground to a particle size of 90 mesh; the ground powder was placed in a microwave device and treated at a power of 400 W for 8 minutes to obtain microwave-treated hydroxyapatite loaded with iron. The purity of diammonium hydrogen phosphate and calcium nitrate was 99%, and the calcium-phosphorus molar ratio Ca / P was 1.67; the purity of iron nitrate was 99%; the mass of the loaded iron element accounted for 10% of the mass of hydroxyapatite; the purity of sodium fluoride was 99%, and the addition amount was 1% of the mass of hydroxyapatite.

[0035] The preparation method of chitosan-bentonite composite adsorbent loaded with aluminum and iron comprises the following steps: Ⅰ. Dissolve chitosan with a deacetylation degree of 90% in an acetic acid solution with a mass percentage concentration of 2% to prepare a chitosan solution with a mass fraction of 2%, and stir until it is completely dissolved; select sodium bentonite, pass it through a 200-mesh sieve to remove large particle impurities; prepare aluminum sulfate and iron sulfate with a purity of 99%; Ⅱ. Add the sieved sodium bentonite to a hydrochloric acid solution with a concentration of 0.8 mol / L, with a solid-liquid ratio of 1:12, and stir the reaction at 70°C for 3 hours to perform activation treatment; after the reaction, centrifuge at a speed of 4500 r / min for 12 minutes, and then dry at 110°C for 7 hours; add the dried sodium bentonite to ionized water to prepare a suspension with a mass fraction of 8%; add a mixed solution of 0.3 mol / L aluminum sulfate and 0.2 mol / L iron sulfate to the bentonite suspension at a stirring speed of 500 r / min, control the reaction temperature at 45°C, and react for 4 hours, wherein the ratio of the amount of aluminum and iron ions to the amount of exchangeable cations in the bentonite is 1:1, and a bentonite suspension loaded with aluminum and iron is obtained; III. Mix the aluminum-iron loaded bentonite suspension with the previously prepared chitosan solution, and continue stirring at 45°C, with a stirring speed of 400 r / min and a stirring time of 8 h; pour the mixed material into a mold to form granules or blocks, and then air-dry at room temperature to a preliminary shape; transfer the preliminary formed material to an oven and dry it at 70°C to constant weight; IV. The dried material was crushed and sieved twice. The first time, a 150-mesh screen was used to remove larger particles. The second time, a 200-mesh screen was used for further screening to obtain chitosan-bentonite composite adsorbent loaded aluminum and iron fine powder with uniform particle size.

[0036] The preparation method of a water treatment defluoridation agent comprises the following steps: (1) Weigh dried lanthanum chloride, cerium sulfate, yttrium acetate, magnesium chloride, zinc chloride, and potassium fluorozirconate respectively, place in a beaker, add deionized water and stir to form a mixed salt solution. Use a magnetic stirrer during the stirring process at a speed of 500 r / min and continue stirring for 2 h; (2) adding cerium-doped titanium dioxide nanotubes into the mixed salt solution, stirring at 400 r / min at 55° C. for 9 h, and continuously introducing nitrogen during the reaction to obtain a mixed solution; (3) Add 4 mol / L ammonia water dropwise to the mixed solution obtained in step (2), adjust the pH value to 9, continue stirring for 7 h, then transfer it to a centrifuge tube, centrifuge it at 10,000 r / min for 25 min, discard the supernatant, and repeatedly wash the precipitate with deionized water 10 times; (4) The washed precipitate was transferred to an oven and dried at 140°C for 10 h, and then placed in a tube furnace and calcined at 600°C for 8 h with nitrogen to obtain a titanium dioxide nanotube intermediate product loaded with lanthanum, cerium, yttrium, magnesium, zinc and zirconium. During the calcination process, the heating rate was 7°C / min and the cooling rate was 5°C / min. (5) The intermediate product is mixed with pretreated activated alumina, diluted and aged polyaluminium chloride ferric, microwave-treated hydroxyapatite loaded with iron, and sieved and graded chitosan-bentonite composite adsorbent loaded with aluminium iron, deionized water is added, and the mixture is stirred at a speed of 1600 r / min for 4 h in a high-speed stirrer. At the same time, sodium polyacrylate is added in an amount of 0.2% of the total mass of the raw materials. The mixed material is dried in an oven at 70°C to constant weight, and then ground into a fine powder with a particle size of 200 mesh, thereby obtaining a water treatment defluoridation agent.

[0037] In step (1) and step (2), the weight proportions of the raw materials are: 12 parts of lanthanum chloride; 10 parts of cerium sulfate; 8 parts of yttrium acetate, 7 parts of magnesium chloride, 5 parts of zinc chloride, 6 parts of potassium fluorozirconate, and 500 parts of deionized water; 40 parts of cerium-doped titanium dioxide nanotubes; in step (5), the amount of activated alumina added after pretreatment is 1.5 times the mass of the intermediate product; the amount of polyaluminum ferric chloride added after dilution and aging is 0.8 times the volume of the intermediate product; the amount of hydroxyapatite loaded with iron added after microwave treatment is 0.3 times the mass of the intermediate product; and the amount of aluminum and iron loaded on the chitosan-bentonite composite adsorbent after sieving and grading is 0.2 times the mass of the intermediate product.

[0038] The purity of lanthanum chloride, cerium sulfate, yttrium acetate, magnesium chloride and zinc chloride is 99%, the purity of potassium fluorozirconate is 98%, the particle size of the pretreated activated alumina is 0.5 mm, and the Al2O3 content in polyaluminium ferric chloride is 6%.

[0039] Example 2 The method for preparing cerium-doped titanium dioxide nanotubes comprises the following steps: ① Mix 0.5g of ammonium fluoride, 5g of deionized water and 95g of ethylene glycol, then add 0.05mol / L of hexadecyltrimethylammonium bromide and continue stirring until completely dissolved to obtain an electrolyte; ②Use titanium foil as anode and platinum sheet as cathode, place them in electrolyte, and carry out anodic oxidation reaction at a constant voltage of 25V for 2h. Keep the electrolyte temperature at 25℃ during the reaction; ③ Take out the anodized sample, rinse it with deionized water, and then soak it in an ethanol solution containing 0.01 mol / L cerium nitrate for 1 h; ④ Dry the sample obtained in step ③ in an oven at 60°C for 12 h, then put it into a tubular furnace, heat it to 550°C at a heating rate of 5°C / min under a nitrogen atmosphere, and calcine it for 3 h to obtain cerium-doped titanium dioxide nanotubes.

[0040] The method for preparing hydroxyapatite loaded with iron after microwave treatment comprises the following steps: a. Synthesis of hydroxyapatite precursor: Weigh calcium nitrate and dissolve it in deionized water to prepare a 0.5 mol / L solution, stir it evenly, and control the temperature at 50°C; dissolve diammonium hydrogen phosphate in another part of deionized water to prepare a 0.3 mol / L solution, stir it evenly, and keep the temperature at 50°C; add the diammonium hydrogen phosphate solution dropwise to the calcium nitrate solution at a stirring speed of 600 r / min, and control the dropping speed at 1 mL / min. After the dropping is completed, continue stirring and react for 3 hours to form a hydroxyapatite precursor suspension; b. Loading iron and fluoride ion doping: Dissolve ferric nitrate in deionized water to prepare a 0.1 mol / L solution, add it to the hydroxyapatite precursor suspension, and continue stirring at a stirring speed of 400 r / min for 2 hours; dissolve the weighed sodium fluoride in deionized water to prepare a 0.05 mol / L solution, add it to the reaction system, and continue stirring for 1 hour to obtain a suspension; c. Precipitation, washing and drying: The suspension obtained in step b was transferred to a centrifuge tube, and centrifuged at 4000 r / min for 15 min to collect the precipitate; the precipitate was repeatedly washed with deionized water for 5 times, and centrifuged again after each washing, and finally the precipitate was washed once with anhydrous ethanol; the washed precipitate was transferred to an oven and dried at 100° C. for 8 h to obtain a dried Fe-HAP powder; d. Grinding and microwave treatment: The dried Fe-HAP powder was ground to a particle size of 150 mesh; the ground powder was placed in a microwave device and treated at a power of 300 W for 6 minutes to obtain microwave-treated hydroxyapatite loaded with iron. The purity of diammonium hydrogen phosphate and calcium nitrate were both 99%, and the calcium-phosphorus molar ratio Ca / P was 1.67; the purity of iron nitrate was 99%; the mass of the loaded iron element accounted for 8% of the mass of hydroxyapatite; the purity of sodium fluoride was 99%, and the addition amount was 0.5% of the mass of hydroxyapatite.

[0041] The preparation method of chitosan-bentonite composite adsorbent loaded with aluminum and iron comprises the following steps: Ⅰ. Dissolve chitosan with a deacetylation degree of 90% in an acetic acid solution with a mass percentage concentration of 3% to prepare a chitosan solution with a mass fraction of 2%, and stir until it is completely dissolved; select sodium bentonite, pass it through a 200-mesh sieve to remove large particle impurities; prepare aluminum sulfate and iron sulfate with a purity of 99%; Ⅱ. Add the sieved sodium bentonite to a 1 mol / L hydrochloric acid solution with a solid-liquid ratio of 1:15, and stir the reaction at 80°C for 3 hours to perform activation treatment; after the reaction, centrifuge at a speed of 5000 r / min for 15 minutes, and then dry at 120°C for 8 hours; add the dried sodium bentonite to ionized water to prepare a suspension with a mass fraction of 10%; add a mixed solution of 0.5 mol / L aluminum sulfate and 0.3 mol / L iron sulfate to the bentonite suspension at a stirring speed of 600 r / min, control the reaction temperature at 50°C, and react for 5 hours, wherein the ratio of the amount of aluminum and iron ions to the amount of exchangeable cations in the bentonite is 1.5:1, and a bentonite suspension loaded with aluminum and iron is obtained; III. Mix the aluminum-iron loaded bentonite suspension with the previously prepared chitosan solution, and continue stirring at 50°C, with a stirring speed of 500 r / min and a stirring time of 10 h; pour the mixed material into a mold to form granules or blocks, and then air-dry at room temperature to a preliminary shape; transfer the preliminary formed material to an oven and dry it at 80°C to constant weight; IV. The dried material was crushed and sieved twice. The first time, a 150-mesh screen was used to remove larger particles. The second time, a 200-mesh screen was used for further screening to obtain chitosan-bentonite composite adsorbent loaded aluminum and iron fine powder with uniform particle size.

[0042] The preparation method of a water treatment defluoridation agent comprises the following steps: (1) Weigh dried lanthanum chloride, cerium sulfate, yttrium acetate, magnesium chloride, zinc chloride, and potassium fluorozirconate respectively, place in a beaker, add deionized water and stir to form a mixed salt solution. Use a magnetic stirrer during the stirring process at a speed of 600 r / min, and continue stirring for 2.5 h; (2) adding cerium-doped titanium dioxide nanotubes into the mixed salt solution, stirring at 60°C and 450 r / min for 9 h, while continuously introducing nitrogen during the reaction, to obtain a mixed solution; (3) Add 4 mol / L ammonia water dropwise to the mixed solution obtained in step (2), adjust the pH value to 10, continue stirring for 7 h, then transfer it to a centrifuge tube, centrifuge it at 10000 r / min for 30 min, discard the supernatant, and repeatedly wash the precipitate with deionized water 15 times; (4) The washed precipitate was transferred to an oven and dried at 150°C for 12 h, and then placed in a tube furnace and calcined at 650°C for 8 h with nitrogen to obtain a titanium dioxide nanotube intermediate product loaded with lanthanum, cerium, yttrium, magnesium, zinc and zirconium. During the calcination process, the heating rate was 7°C / min and the cooling rate was 5°C / min. (5) The intermediate product is mixed with pretreated activated alumina, diluted and aged polyaluminium chloride ferric, microwave-treated hydroxyapatite loaded with iron, and sieved and graded chitosan-bentonite composite adsorbent loaded with aluminium iron, deionized water is added, and the mixture is stirred at a speed of 1800 r / min in a high-speed stirrer for 5 h. At the same time, sodium polyacrylate is added in an amount of 0.2% of the total mass of the raw materials. The mixed material is dried in an oven at 75°C to constant weight, and then ground into a fine powder with a particle size of 180 mesh, thereby obtaining a water treatment defluoridation agent.

[0043] In step (1) and step (2), the weight proportions of the raw materials are: lanthanum chloride: 15 parts; cerium sulfate: 12 parts; yttrium acetate: 10 parts, magnesium chloride: 8 parts, zinc chloride: 6 parts, potassium fluorozirconate: 7 parts, and deionized water: 600 parts; cerium-doped titanium dioxide nanotubes: 42 parts; in step (5), the amount of activated alumina added after pretreatment is 1.8 times the mass of the intermediate product; the amount of polyaluminum ferric chloride added after dilution and aging is 1 times the volume of the intermediate product; the amount of hydroxyapatite loaded with iron added after microwave treatment is 0.3 times the mass of the intermediate product; and the amount of aluminum and iron loaded on the chitosan-bentonite composite adsorbent after sieving and grading is 0.25 times the mass of the intermediate product.

[0044] The purity of lanthanum chloride, cerium sulfate, yttrium acetate, magnesium chloride and zinc chloride is 99%, the purity of potassium fluorozirconate is 98%, the particle size of activated alumina after pretreatment is 1 mm, and the Al2O3 content in polyaluminium ferric chloride is 7%.

[0045] Example 3 The method for preparing cerium-doped titanium dioxide nanotubes comprises the following steps: ① Mix 0.5g of ammonium fluoride, 5g of deionized water and 95g of ethylene glycol, then add 0.05mol / L of hexadecyltrimethylammonium bromide and continue stirring until completely dissolved to obtain an electrolyte; ②Use titanium foil as anode and platinum sheet as cathode, place them in electrolyte, and carry out anodic oxidation reaction at a constant voltage of 25V for 2h. Keep the electrolyte temperature at 25℃ during the reaction; ③ Take out the anodized sample, rinse it with deionized water, and then soak it in an ethanol solution containing 0.01 mol / L cerium nitrate for 2 h; ④ Dry the sample obtained in step ③ in an oven at 60°C for 12 h, then put it into a tubular furnace, heat it to 550°C at a heating rate of 5°C / min under a nitrogen atmosphere, and calcine it for 3 h to obtain cerium-doped titanium dioxide nanotubes.

[0046] The method for preparing hydroxyapatite loaded with iron after microwave treatment comprises the following steps: a. Synthesis of hydroxyapatite precursor: Weigh calcium nitrate and dissolve it in deionized water to prepare a 1 mol / L solution, stir it evenly, and control the temperature at 60°C; dissolve diammonium hydrogen phosphate in another part of deionized water to prepare a 0.6 mol / L solution, stir it evenly, and keep the temperature at 60°C; add the diammonium hydrogen phosphate solution dropwise to the calcium nitrate solution at a stirring speed of 800 r / min, and control the dropping speed at 3 mL / min. After the dropping is completed, continue to stir and react for 5 hours to form a hydroxyapatite precursor suspension; b. Loading iron and fluoride ion doping: Dissolve ferric nitrate in deionized water to prepare a 0.3 mol / L solution, add it to the hydroxyapatite precursor suspension, and continue stirring at a stirring speed of 600 r / min for 3 hours; dissolve the weighed sodium fluoride in deionized water to prepare a 0.1 mol / L solution, add it to the reaction system, and continue stirring for 2 hours to obtain a suspension; c. Precipitation, washing and drying: The suspension obtained in step b was transferred to a centrifuge tube, and centrifuged at 6000 r / min for 25 min to collect the precipitate; the precipitate was repeatedly washed with deionized water for 8 times, and centrifuged again after each washing, and finally the precipitate was washed twice with anhydrous ethanol; the washed precipitate was transferred to an oven and dried at 120° C. for 12 h to obtain a dried Fe-HAP powder; d. Grinding and microwave treatment: The dried Fe-HAP powder was ground to a particle size of 200 meshes; the ground powder was placed in a microwave device and treated at a power of 500 W for 10 minutes to obtain microwave-treated hydroxyapatite loaded with iron. The purity of diammonium hydrogen phosphate and calcium nitrate were both 99%, and the calcium-phosphorus molar ratio Ca / P was 1.67; the purity of iron nitrate was 99%; the mass of the loaded iron element accounted for 12% of the mass of hydroxyapatite; the purity of sodium fluoride was 99%, and the addition amount was 2% of the mass of hydroxyapatite.

[0047] The preparation method of chitosan-bentonite composite adsorbent loaded with aluminum and iron comprises the following steps: Ⅰ. Dissolve chitosan with a deacetylation degree of 90% in an acetic acid solution with a mass percentage concentration of 1% to prepare a chitosan solution with a mass fraction of 1%, and stir until it is completely dissolved; select sodium bentonite, pass it through a 200-mesh sieve to remove large particle impurities; prepare aluminum sulfate and iron sulfate with a purity of 99%; Ⅱ. Add the sieved sodium bentonite to a hydrochloric acid solution with a concentration of 0.5 mol / L, with a solid-liquid ratio of 1:10, and stir the reaction at 60°C for 2 hours to perform activation treatment; after the reaction, centrifuge at a speed of 4000 r / min for 10 minutes, and then dry at 100°C for 6 hours; add the dried sodium bentonite to ionized water to prepare a suspension with a mass fraction of 5%; add a mixed solution of 0.1 mol / L aluminum sulfate and 0.05 mol / L iron sulfate to the bentonite suspension at a stirring speed of 400 r / min, control the reaction temperature at 40°C, and react for 3 hours, wherein the ratio of the amount of aluminum and iron ions to the amount of exchangeable cations in the bentonite is 0.5:1, and a bentonite suspension loaded with aluminum and iron is obtained; III. Mix the aluminum-iron loaded bentonite suspension with the previously prepared chitosan solution, and continue stirring at 40°C, with a stirring speed of 300 r / min and a stirring time of 6 h; pour the mixed material into a mold to form granules or blocks, and then air-dry at room temperature to a preliminary shape; transfer the preliminary formed material to an oven and dry it at 60°C to constant weight; IV. The dried material was crushed and sieved twice. The first time, a 150-mesh screen was used to remove larger particles. The second time, a 200-mesh screen was used for further screening to obtain chitosan-bentonite composite adsorbent loaded aluminum and iron fine powder with uniform particle size.

[0048] The preparation method of a water treatment defluoridation agent comprises the following steps: (1) Weigh dried lanthanum chloride, cerium sulfate, yttrium acetate, magnesium chloride, zinc chloride, and potassium fluorozirconate respectively, place in a beaker, add deionized water and stir to form a mixed salt solution. Use a magnetic stirrer during the stirring process at a speed of 400 r / min, and continue stirring for 1.5 h; (2) adding cerium-doped titanium dioxide nanotubes into a mixed salt solution, stirring at 50° C. and 350 r / min for 7 h, while continuously introducing nitrogen during the reaction, to obtain a mixed solution; (3) Add 3 mol / L ammonia water dropwise to the mixed solution obtained in step (2), adjust the pH value to 9, continue stirring for 5 h, then transfer it to a centrifuge tube, centrifuge it at 8000 r / min for 20 min, discard the supernatant, and repeatedly wash the precipitate with deionized water 8 times; (4) The washed precipitate was transferred to an oven and dried at 130°C for 8 h, and then placed in a tube furnace and calcined at 550°C for 6 h with nitrogen to obtain a titanium dioxide nanotube intermediate product loaded with lanthanum, cerium, yttrium, magnesium, zinc and zirconium. During the calcination process, the heating rate was 5°C / min and the cooling rate was 3°C / min. (5) The intermediate product is mixed with pretreated activated alumina, diluted and aged polyaluminium chloride ferric, microwave-treated hydroxyapatite loaded with iron, and sieved and graded chitosan-bentonite composite adsorbent loaded with aluminium iron, deionized water is added, and the mixture is stirred at a speed of 1200 r / min for 3 h in a high-speed stirrer. At the same time, sodium polyacrylate is added in an amount of 0.1% of the total mass of the raw materials. The mixed material is dried in an oven at 65°C to constant weight, and then ground into a fine powder with a particle size of 200 mesh, thereby obtaining a water treatment defluorination agent.

[0049] In step (1) and step (2), the weight proportions of the raw materials are: 10 parts of lanthanum chloride; 6 parts of cerium sulfate; 7 parts of yttrium acetate, 6 parts of magnesium chloride, 4 parts of zinc chloride, 5 parts of potassium fluorozirconate, and 400 parts of deionized water; 35 parts of cerium-doped titanium dioxide nanotubes; in step (5), the amount of activated alumina added after pretreatment is 1.2 times the mass of the intermediate product; the amount of polyaluminum ferric chloride added after dilution and aging is 0.6 times the volume of the intermediate product; the amount of hydroxyapatite loaded with iron added after microwave treatment is 0.2 times the mass of the intermediate product; and the amount of chitosan-bentonite composite adsorbent loaded with aluminum and iron added after sieving and grading is 0.15 times the mass of the intermediate product.

[0050] The purity of lanthanum chloride, cerium sulfate, yttrium acetate, magnesium chloride and zinc chloride is 99%, the purity of potassium fluorozirconate is 98%, the particle size of the pretreated activated alumina is 0.2 mm, and the Al2O3 content in polyaluminium ferric chloride is 5%.

[0051] Comparative Example 1 Compared with Example 1, the difference is that: cerium sulfate, yttrium acetate and zinc chloride are not added; the amount of lanthanum chloride added is the sum of the masses of lanthanum chloride, cerium sulfate and yttrium acetate, and the amount of magnesium chloride added is the sum of the masses of magnesium chloride and zinc chloride.

[0052] Comparative Example 2 Compared with Example 2, the difference is that the titanium dioxide nanotubes are not doped with cerium and ammonium fluoride is not added.

[0053] Comparative Example 3 Compared with Example 3, the difference is that: no activated alumina and polyaluminium ferric chloride are added, and the amount of hydroxyapatite loaded iron added is the sum of the masses of pretreated activated alumina, diluted and aged polyaluminium ferric chloride, and microwave-treated hydroxyapatite loaded iron.

[0054] Comparative Example 4 Compared with Example 1, the difference is that the microwave-treated hydroxyapatite loaded with iron is not added.

[0055] Comparative Example 5 Compared with Example 1, the difference is that no sieved and graded chitosan-bentonite composite adsorbent loaded with aluminum and iron is added.

[0056] Application Example 1 The application method of the water treatment defluoridation agent comprises the following steps: A. After the wastewater is treated with sodium sulfide, the concentration of fluoride ions in the etching wastewater is accurately determined to be 250 mg / L by ion chromatography; the concentrations of copper and iron ions are determined by atomic absorption spectroscopy; EDTA-2Na is weighed at twice the total molar amount of copper and iron ions; it is prepared into a 2 mol / L solution, added to the etching wastewater at a stirring speed of 300 r / min, reacted for 25 minutes, and the pH value is adjusted to 7 using a 2 mol / L hydrochloric acid solution; B. Add the defluorination agent obtained in Example 1 at a dosage of 6 g / L; C. Maintain the reaction temperature at 30°C and the reaction time at 120 min; use mechanical or magnetic stirring, and control the stirring speed at 300 r / min; set the speed at 350 r / min at the beginning, and adjust it to 280 r / min after 30 min of reaction; D. 30 minutes after the reaction starts, add nano-silicon dioxide at 4% of the mass of the defluorinating agent; the nano-silicon dioxide is ultrasonically dispersed in anhydrous ethanol in advance, the ultrasonic power is 300W, and the ultrasonication is carried out for 35 minutes; stirring is continued for 35 minutes after addition; when the defluorination reaction is carried out for 60 minutes, a polyacrylamide solution with a mass percentage concentration of 2% is added, and the dosage is 1mL / L; after the addition of the polyacrylamide solution, a polydopamine solution is added at 2% of the total mass of the system; the polydopamine solution is prepared by stirring dopamine hydrochloride in a Tris-HCl buffer solution at room temperature for 24 hours, and stirring is carried out for 30 minutes after addition, wherein the pH of the Tris-HCl buffer solution is 8.5; E. After stopping stirring, let it stand and settle for 50 minutes; then use 0.5μm filter paper to filter at normal pressure; then transfer the filtrate to a centrifuge tube and centrifuge at 5000r / min for 15 minutes to separate the remaining fine particles and obtain treated water.

[0057] Application Example 2 The application method of the water treatment defluoridation agent comprises the following steps: A. After the wastewater is treated with sodium sulfide, the concentration of fluoride ions in the etching wastewater is accurately determined to be 525 mg / L using ion chromatography; the concentrations of copper and iron ions are determined by atomic absorption spectroscopy; EDTA-2Na is weighed at twice the total molar amount of copper and iron ions; it is prepared into a 0.2 mol / L solution, and the etching wastewater is added at a stirring speed of 300 r / min, and the reaction is carried out for 30 minutes. If the pH value of the wastewater increases after being treated with sodium sulfide, the pH value is adjusted to 8 using a 2 mol / L hydrochloric acid solution; B. Add the defluorination agent obtained in Example 2 at a dosage of 8 g / L; C. Maintain the reaction temperature at 35°C and the reaction time at 150 min; use mechanical or magnetic stirring, and control the stirring speed at 350 r / min; set the speed at 350 r / min at the beginning, and adjust it to 300 r / min after 30 min of reaction; D. 30 minutes after the reaction starts, add nano-silicon dioxide at 3% of the mass of the defluorinating agent; the nano-silicon dioxide is ultrasonically dispersed in anhydrous ethanol in advance, the ultrasonic power is 250W, and the ultrasonication is carried out for 30 minutes; stirring is continued for 30 minutes after addition; when the defluorination reaction is carried out for 60 minutes, a polyacrylamide solution with a mass percentage concentration of 0.1% is added, and the addition amount is 0.5mL / L; after adding the polyacrylamide solution, a polydopamine solution is added at 1% of the total mass of the system; the polydopamine solution is prepared by stirring dopamine hydrochloride in a Tris-HCl buffer solution at room temperature for 24 hours, and stirring is carried out for 20 minutes after addition, wherein the pH of the Tris-HCl buffer solution is 8.5; E. After stopping stirring, let it stand and settle for 45 minutes; then use 0.45μm filter paper to filter at normal pressure; then transfer the filtrate to a centrifuge tube and centrifuge at 4000r / min for 10 minutes to separate the remaining fine particles and obtain treated water.

[0058] Application Example 3 The application method of the water treatment defluoridation agent comprises the following steps: A. After the wastewater is treated with sodium hydroxide, the concentration of fluoride ions in the etching wastewater is accurately determined to be 830 mg / L using ion chromatography; the concentrations of copper and iron ions are determined by atomic absorption spectroscopy; EDTA-2Na is weighed according to 1.5 times the total molar amount of copper and iron ions; it is prepared into a 0.1 mol / L solution, and the etching wastewater is added at a stirring speed of 300 r / min, and the reaction is carried out for 20 minutes. If the pH value of the wastewater increases after being treated with sodium sulfide, the pH value is adjusted to 6 using a 1 mol / L hydrochloric acid solution; B. Add the defluorination agent obtained in Example 3, with a dosage of 11 g / L; C. Maintain the reaction temperature at 25°C and the reaction time at 90 minutes; use mechanical or magnetic stirring, and control the stirring speed at 250r / min; set the speed at 350r / min at the beginning, and adjust it to 250r / min after 30 minutes of reaction; D. 30 minutes after the reaction starts, add nano-silicon dioxide at 5% of the mass of the defluorinating agent; the nano-silicon dioxide is ultrasonically dispersed in anhydrous ethanol in advance, the ultrasonic power is 350W, and the ultrasonication is performed for 40 minutes; stirring is continued for 40 minutes after addition; when the defluorination reaction is carried out for 60 minutes, a polyacrylamide solution with a mass percentage concentration of 0.3% is added, and the dosage is 1.5mL / L; after the addition of the polyacrylamide solution, a polydopamine solution is added at 2% of the total mass of the system; the polydopamine solution is prepared by stirring dopamine hydrochloride in a Tris-HCl buffer solution at room temperature for 24 hours, and stirring is performed for 30 minutes after addition, wherein the pH of the Tris-HCl buffer solution is 8.5; E. After stopping stirring, let it stand and settle for 60 minutes; then use 0.6μm filter paper to filter at normal pressure; then transfer the filtrate to a centrifuge tube and centrifuge at 6000r / min for 20 minutes to separate the remaining fine particles and obtain treated water.

[0059] Application Comparative Example 1 The difference from Application Example 1 is that the defluorination agent obtained in Comparative Example 1 is used.

[0060] Application Comparative Example 2 The difference from Application Example 2 is that the defluorination agent obtained in Comparative Example 2 is used.

[0061] Application Comparative Example 3 The difference from Application Example 3 is that the defluorination agent obtained in Comparative Example 3 is used.

[0062] Application Comparative Example 4 The difference from Application Example 3 is that the defluorination agent obtained in Comparative Example 4 is used.

[0063] Application Comparative Example 5 The difference from Application Example 3 is that the defluorination agent obtained in Comparative Example 5 is used.

[0064] Application Comparative Example 6 The difference from Application Example 1 is that no nano silicon dioxide is added.

[0065] Application Comparative Example 7 The difference from Application Example 1 is that EDTA-2Na and polyacrylamide solution are not added.

[0066] The test data of application examples 1-3 and application comparative examples 1-7 are shown in Table 1.

[0067] Table 1 Test data of application examples 1-3 and application comparative examples 1-7

[0068] It can be seen from the above data that the defluorination agent prepared by the present invention has excellent defluorination performance, and the defluorination rate can reach more than 99%. It has obvious treatment effect on fluorine-containing wastewater with high copper and iron ion content, and has the function of removing copper and iron ions at the same time, and the effect is obvious. The wastewater after defluorination meets the emission standard of fluoride ion concentration below 10 mg / L after treatment.

Claims

1. A method for preparing a water treatment defluorination agent, characterized in that: The following steps are involved: (1) Weigh dried lanthanum chloride, cerium sulfate, yttrium acetate, magnesium chloride, zinc chloride, and potassium fluorozirconate respectively, place in a beaker, add deionized water and stir to form a mixed salt solution. Use a magnetic stirrer during the stirring process at a speed of 400-600 r / min, and continue stirring for 1.5-2.5 hours; (2) adding cerium-doped titanium dioxide nanotubes to a mixed salt solution, stirring at 50-60° C. at a speed of 350-450 r / min for 7-9 hours, and continuously introducing nitrogen during the reaction to obtain a mixed solution; (3) Add 3-4 mol / L ammonia water dropwise to the mixed solution obtained in step (2), adjust the pH value to 9-10, continue stirring for 5-7 hours, then transfer it to a centrifuge tube, centrifuge it at a speed of 8000-10000 r / min for 20-30 minutes, discard the supernatant, and repeatedly wash the precipitate with deionized water for 8-15 times; (4) The washed precipitate is transferred to an oven, dried at 130-150°C for 8-12 hours, and then placed in a tube furnace and calcined at 550-650°C for 6-8 hours with nitrogen to obtain a titanium dioxide nanotube intermediate product loaded with lanthanum, cerium, yttrium, magnesium, zinc and zirconium. During the calcination process, the heating rate is 5-7°C / min and the cooling rate is 3-5°C / min; (5) The intermediate product is mixed with pretreated activated alumina, diluted and aged polyaluminium chloride ferric, microwave-treated hydroxyapatite loaded with iron, and sieved and graded chitosan-bentonite composite adsorbent loaded with aluminium iron, deionized water is added, and the mixture is stirred at a speed of 1200-1800 r / min for 3-5 hours in a high-speed stirrer. At the same time, sodium polyacrylate is added in an amount of 0.1%-0.2% of the total mass of the raw materials. The mixed material is dried in an oven at 65-75°C to constant weight, and then ground into fine powder with a particle size of less than 160 mesh, thereby obtaining a water treatment defluoridation agent.

2. The method for preparing a water treatment defluoridation agent according to claim 1, characterized in that: In the steps (1) and (2), the weight proportions of the raw materials are as follows: 10-15 parts of lanthanum chloride; 6-12 parts of cerium sulfate; 7-10 parts of yttrium acetate, 6-8 parts of magnesium chloride, 4-6 parts of zinc chloride, 5-7 parts of potassium fluorozirconate, and 400-600 parts of deionized water; 35-42 parts of cerium-doped titanium dioxide nanotubes; in the step (5), the amount of activated alumina added after pretreatment is 1.2-1.8 times the mass of the intermediate product; the amount of polyaluminium ferric chloride added after dilution and aging is 0.6-1 times the volume of the intermediate product; the amount of hydroxyapatite loaded with iron added after microwave treatment is 0.2-0.3 times the mass of the intermediate product; and the amount of chitosan-bentonite composite adsorbent loaded with aluminium and iron added after sieving and grading is 0.15-0.25 times the mass of the intermediate product.

3. The method for preparing a water treatment defluoridation agent according to claim 1, characterized in that: The purity of the lanthanum chloride, cerium sulfate, yttrium acetate, magnesium chloride and zinc chloride is greater than or equal to 99%, the purity of potassium fluorozirconate is ≥98%, the particle size of the pretreated activated alumina is 0.2-1mm, and the Al2O3 content in the polyaluminum ferric chloride is 5%-7%.

4. The method for preparing a water treatment defluorination agent according to claim 1, characterized in that: The method for preparing cerium-doped titanium dioxide nanotubes comprises the following steps: ① Mix 0.5g of ammonium fluoride, 5g of deionized water and 95g of ethylene glycol, then add 0.05mol / L of hexadecyltrimethylammonium bromide and continue stirring until completely dissolved to obtain an electrolyte; ②Use titanium foil as anode and platinum sheet as cathode, place them in electrolyte, and carry out anodic oxidation reaction at a constant voltage of 25V for 2h. Keep the electrolyte temperature at 25℃ during the reaction; ③ Take out the anodized sample, rinse it with deionized water, and then soak it in an ethanol solution containing 0.01 mol / L cerium nitrate for 1-2 hours; ④ Dry the sample obtained in step ③ in an oven at 60-65°C for 12 hours, then place it in a tubular furnace, heat it to 550°C at a heating rate of 5°C / min under a nitrogen atmosphere, and calcine it for 3 hours to obtain cerium-doped titanium dioxide nanotubes.

5. The method for preparing a water treatment defluoridation agent according to claim 1, characterized in that: The method for preparing the microwave-treated hydroxyapatite loaded with iron comprises the following steps: a. Synthesis of hydroxyapatite precursor: Weigh calcium nitrate and dissolve it in deionized water to prepare a 0.5-1 mol / L solution, stir it evenly, and control the temperature at 50-60°C; dissolve diammonium hydrogen phosphate in another part of deionized water to prepare a 0.3-0.6 mol / L solution, stir it evenly, and keep the temperature at 50-60°C; add the diammonium hydrogen phosphate solution dropwise to the calcium nitrate solution at a stirring speed of 600-800 r / min, and control the dropping speed at 1-3 mL / min. After the dropping is completed, continue to stir and react for 3-5 hours to form a hydroxyapatite precursor suspension; b. Loading iron and fluoride ion doping: Dissolve ferric nitrate in deionized water to prepare a 0.1-0.3 mol / L solution, add it to the hydroxyapatite precursor suspension, and continue stirring at a speed of 400-600 r / min for 2-3 hours; dissolve the weighed sodium fluoride in deionized water to prepare a 0.05-0.1 mol / L solution, add it to the reaction system, and continue stirring for 1-2 hours to obtain a suspension; c. Precipitation, washing and drying: The suspension obtained in step b is transferred to a centrifuge tube, centrifuged at a speed of 4000-6000 r / min for 15-25 min, and the precipitate is collected; the precipitate is repeatedly washed with deionized water for 5-8 times, centrifuged again after each washing, and finally the precipitate is washed with anhydrous ethanol for 1-2 times; the washed precipitate is transferred to an oven, and dried at 100-120° C. for 8-12 h to obtain a dried Fe-HAP powder; d. Grinding and microwave treatment: The dried Fe-HAP powder is ground to a particle size less than 100 meshes; the ground powder is placed in a microwave device and treated at a power of 300-500W for 6-10 minutes to obtain microwave-treated hydroxyapatite loaded with iron.

6. The method for preparing a water treatment defluoridation agent according to claim 5, characterized in that: The purity of the diammonium hydrogen phosphate and calcium nitrate is greater than or equal to 99%, and the calcium-phosphorus molar ratio Ca / P is 1.67; the purity of the ferric nitrate is ≥99%; the mass of the loaded iron element accounts for 8%-12% of the mass of the hydroxyapatite; the purity of the sodium fluoride is ≥99%, and the added amount is 0.5%-2% of the mass of the hydroxyapatite.

7. The method for preparing a water treatment defluorination agent according to claim 1, characterized in that: The preparation method of the chitosan-bentonite composite adsorbent loaded with aluminum and iron comprises the following steps: Ⅰ. Dissolve chitosan with a deacetylation degree of ≥90% in an acetic acid solution with a mass percentage concentration of 1%-3% to prepare a chitosan solution with a mass fraction of 1%-2%, and stir until it is completely dissolved; select sodium bentonite, pass it through a 200-mesh sieve to remove large particle impurities; prepare aluminum sulfate and iron sulfate with a purity of ≥99%; Ⅱ. Add the sieved sodium bentonite to a hydrochloric acid solution with a concentration of 0.5-1 mol / L, with a solid-liquid ratio of 1:(10-15), and stir the reaction at 60-80°C for 2-3 hours to perform activation treatment; after the reaction, centrifuge at a speed of 4000-5000 r / min for 10-15 minutes, and then dry at 100-120°C for 6-8 hours; add the dried sodium bentonite to ionized water to prepare a mass fraction of 5 %-10% suspension; under a stirring speed of 400-600r / min, a mixed solution of 0.1-0.5mol / L aluminum sulfate and 0.05-0.3mol / L ferric sulfate is added to the bentonite suspension, the reaction temperature is controlled at 40-50°C, the reaction time is 3-5h, wherein the ratio of the amount of aluminum and iron ions to the amount of exchangeable cations in the bentonite is (0.5-1.5): 1, to obtain an aluminum and iron loaded bentonite suspension; III. Mix the aluminum-iron loaded bentonite suspension with the previously prepared chitosan solution, and continue stirring at 40-50°C, at a stirring speed of 300-500r / min, for 6-10h; pour the mixed material into a mold to form granules or blocks, and then air-dry at room temperature to a preliminary shape; transfer the preliminary formed material to an oven and dry it at 60-80°C to constant weight; IV. The dried material was crushed and sieved twice. The first time, a 150-mesh screen was used to remove larger particles. The second time, a 200-mesh screen was used for further screening to obtain chitosan-bentonite composite adsorbent loaded aluminum and iron fine powder with uniform particle size.

8. A water treatment defluorination agent, characterized in that: The defluoridation agent for water treatment is prepared by the preparation method of any one of claims 1 to 7.

9. An application of the water treatment defluorination agent according to claim 8, characterized in that: Used to remove fluorine from wastewater containing fluorine, copper and iron ions generated by the etching process in the semiconductor chip manufacturing process.

10. The use of the water treatment defluorination agent according to claim 9, characterized in that: The defluorination process comprises the following steps: A. Use ion chromatography to accurately determine the concentration of fluoride ions in etching wastewater, which is between 100-1000 mg / L; determine the concentration of copper and iron ions by atomic absorption spectroscopy; determine the pH value of wastewater; weigh EDTA-2Na according to 1.5-2 times the total molar amount of copper and iron ions; prepare it into a 0.1-0.2 mol / L solution, add etching wastewater at a stirring speed of 300 r / min, and react for 20-30 minutes. If the pH value of the wastewater increases after treatment, use 1-2 mol / L hydrochloric acid solution to adjust the pH value to 6-8; if the pH value does not change much and is within the range of 6-8, no adjustment is required; B. According to the measured fluoride ion concentration, determine the dosage of the defluoridation agent: when the fluoride ion concentration is 100-300mg / L, the dosage is 4-6g / L; when it is 300-600mg / L, the dosage is 6-8g / L; when it is 600-1000mg / L, the dosage is 8-12g / L; C. Maintain the reaction temperature at 25-35°C and the reaction time at 90-150min; use mechanical or magnetic stirring, and control the stirring speed at 250-350r / min; set the speed at 350r / min at the beginning, and adjust it to 250-300r / min after 30min of reaction; D. 30 minutes after the reaction starts, add nano-silicon dioxide according to the mass of the defluorinating agent at 3%-5%; the nano-silicon dioxide is ultrasonically dispersed in anhydrous ethanol in advance, the ultrasonic power is 250-350W, and the ultrasonication is carried out for 30-40 minutes; stirring is continued for 30-40 minutes after addition; when the defluorination reaction is carried out for 60 minutes, a polyacrylamide solution with a mass percentage concentration of 0.1%-0.3% is added, and the addition amount is 0.5-1.5mL / L; after adding the polyacrylamide solution, a polydopamine solution is added according to the total mass of the system at 1%-2%; the polydopamine solution is prepared by stirring dopamine hydrochloride in a Tris-HCl buffer solution at room temperature for 24 hours, and stirring is carried out for 20-30 minutes after addition, wherein the pH of the Tris-HCl buffer solution is 8.5; E. After stopping stirring, let it stand and settle for 45-60 minutes; then use filter paper with a pore size of 0.45-0.6μm to filter at normal pressure; then transfer the filtrate to a centrifuge tube and centrifuge it at a speed of 4000-6000r / min for 10-20min to separate the remaining fine particles and obtain treated water.

Citation Information

Patent Citations

  • Preparation method for double-rare earth element lanthanum and gadolinium codoped titanium dioxide nanotube

    CN103071479A

  • Refuse leachate pretreatment process

    CN107021582A

  • Soil passivator for repairing lead-cadmium-arsenic combined pollution and preparation method and application thereof

    CN113429975A

  • Preparation method and application of rare earth cerium doped titanium dioxide nanotube array structure material

    CN114411190A

  • Strong adsorption-flocculation composite material and preparation method thereof

    CN115925032A

Cited By

  • Photovoltaic wastewater treatment agent and preparation method thereof

    CN120885187A

  • Efficient fluorine removal agent with adsorption-chelation dual functions

    CN120964927A

  • Preparation method and application of fluorine removal agent

    CN121244185A